Penerapan Metode Analisis Regresi Linier Pada Faktor-Faktor Penguasaan Kosa Kata Bahasa Inggris Mahasiswa - Fauzan Hari Sudding Sally; Muhammad Fahmuddin S (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2023)
This research aims to determine whether social media and students’ motivation to learn significantly affect students’ English vocabulary mastery using regression analysis. The findings indicate that students’ motivation to know has a significant effect on students' English vocabulary mastery. The coefficient of determination obtained is 0.301, which means that the motivation to learn variable can explain the vocabulary mastery variable by 30.1%. In comparison, the remaining 69.9% is explained by other variables not included in this research. However, there is no significant relationship was found between the use of social media by the students and their English vocabulary mastery